Preparation of polymer-clay nanocomposites using emulsion polymerization : influence of clay modifiers on the final nanocomposites morphology - Greesh, Nagi Giuma (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 2006.